Oral Function and the Oral Microbiome in the Elderly in the Kyotango Area - Yoshiaki Yamamoto; Toshiro Yamamoto; Nao Miyamoto; Kohei Kinoshita; Satomi Nishikawa; Tetsuya Adachi; Shigeta Takizawa; Ryo Inoue; Satoaki Matoba; Narisato Kanamura (MDPI AG, 2024)
Introduction: Prevention of tooth loss contributes to an extended life expectancy, namely longevity. Aging-related oral hypofunction, including tooth loss, markedly increases the risks of functional disorder and mortality. Dysbiosis of the oral microbiome has recently been associated with various diseases, such as liver cirrhosis, pancreatic cancer, colorectal cancer, and inflammatory bowel disease. Therefore, the relationship between the oral microbiome and systemic health has been attracting increasing attention. In the present study, we examined oral function and the oral microbiome in the elderly in a world-leading longevity area. Materials and Methods: An oral examination, chewing ability/tongue-lip motor function/saliva tests, and a metagenomic analysis with a 16S rRNA gene-targeting next-generation sequencer were conducted on 78 subjects aged ≥80 years. Twenty-six healthy individuals aged between 20 and 39 years were also investigated as controls. The data obtained were statistically analyzed. The protocol of the present study was approved by the Ethics Review Board of our university (ERB-C-885). Results: Chewing ability, tongue-lip motor function, and saliva volume were normal in elderly subjects with a current tooth number ≥20, but were significantly lower in those with a current tooth number <20. The oral microbiome in elderly subjects with a current tooth number ≥20 and young controls differed from that in elderly subjects with a current tooth number <20. Conclusion: Tooth number ≥20 in elderly subjects in the longevity area contributed to the maintenance of both oral function and the diversity of the oral microbiome.